2003
DOI: 10.1094/pdis.2003.87.3.233
|View full text |Cite
|
Sign up to set email alerts
|

New Amylase Inhibitor Present in Corn Seeds Active In Vitro Against Amylase from Fusarium verticillioides

Abstract: A screening for specific amylase inhibitor levels against amylase from Fusarium verticillioides (Fusarium moniliforme), the most relevant mycotoxigenic fungus in corn, was conducted on 37 corn hybrids. The amylase inhibitor levels in these hybrids ranged from 5.5 to 16.0 amylase inhibitor units per gram of corn (AIU/g) in the MASTER and AG5011 hybrids, respectively. The hybrid with the maximum content of inhibitor was used as the source of this new protein. The inhibitor was partially purified using fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
3
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
8
3
6
Order By: Relevance
“…A high level of fumonisin contamination was detected in the corn samples from the Northern (range 0.57 to 20.38 µg/g) and the Central-Western (range 0.32 to 15.86 µg/g) regions, when compared to the Central-Southern 0.13 to 3.66 µg/g (data not shown). These fumonisin levels were lower than those reported in freshly harvested and stored corn samples from Ribeirão Preto, São Paulo State (Orsi et al, 2000), but higher than those reported by Figueira et al (2003) for 37 corn samples from the Northern region of Paraná State (range 0.05 to 2.67 µg/g). Figueira et al (2003) detected lower fumonisin levels in corn samples probably due to the immediate drying after harvesting.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…A high level of fumonisin contamination was detected in the corn samples from the Northern (range 0.57 to 20.38 µg/g) and the Central-Western (range 0.32 to 15.86 µg/g) regions, when compared to the Central-Southern 0.13 to 3.66 µg/g (data not shown). These fumonisin levels were lower than those reported in freshly harvested and stored corn samples from Ribeirão Preto, São Paulo State (Orsi et al, 2000), but higher than those reported by Figueira et al (2003) for 37 corn samples from the Northern region of Paraná State (range 0.05 to 2.67 µg/g). Figueira et al (2003) detected lower fumonisin levels in corn samples probably due to the immediate drying after harvesting.…”
Section: Resultscontrasting
confidence: 68%
“…These fumonisin levels were lower than those reported in freshly harvested and stored corn samples from Ribeirão Preto, São Paulo State (Orsi et al, 2000), but higher than those reported by Figueira et al (2003) for 37 corn samples from the Northern region of Paraná State (range 0.05 to 2.67 µg/g). Figueira et al (2003) detected lower fumonisin levels in corn samples probably due to the immediate drying after harvesting. Such a procedure probably prevented fungal growth during the interval between harvesting and drying, where the critical fumonisin production occurs, i.e.…”
Section: Resultscontrasting
confidence: 68%
“…Posteriormente extraiu-se o inibidor de amilase, presente nos grãos de milho, com etanol. A extração foi realizada segundo metodologia utilizada por Figueira et al (2003a A extração do inibidor de amilase, presente nos grãos de milho, com tampão acetato de sódio 0,1 M, foi realizada conforme metodologia utilizada por Figueira et al (2003b). A farinha de milho, com granulometria de 48 mesh, foi desengordurada por homogeneização com acetona na proporção 1:1 (p/v), durante 15 min.…”
Section: Methodsunclassified
“…O de 23,8 kDa inibe as α-amilases de Acanthoscelides obtectus (Say) e Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae), Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) e T. castaneum (Figueira et al 2003a). O outro, de 19,7 kDa, inibe as α-amilases de S. zeamais, P. truncatus, A. obtectus e Z. subfasciatus (Figueira et al 2003b).…”
mentioning
confidence: 99%
“…As plantas, por sua vez, possuem uma série de compostos que estão associados com a resistência à fatores bióticos e abióticos, como insetos e fungos. A tecnologia do uso de inibidores de enzimas digestivas como fator de resistência, tem chamado a atenção de vários pesquisadores 3,4,5 A inibição do crescimento micelial do patógeno foi avaliada durante os 7 dias, medindo o diâmetro da colônia do fungo, com 3 medições em sentidos perpendicularmente opostos, nos experimentos com extratos inibidor e nos controles. O conteúdo de glicosamina 6 e a inibição da atividade da enzima α amilase também foram determinados para avaliar a ação dos extratos 7 .…”
Section: Introductionunclassified